A Cost-Effective Methodology for Sizing Solar PV Systems for Existing Irrigation Facilities in Chile - Aldo Barrueto Guzmán; Rodrigo Barraza Vicencio; Jorge Alfredo Ardila-Rey; Eduardo Núñez Ahumada; Arturo González Araya; Gerardo Arancibia Moreno (Energies, 2018)
In the last five years, the Chilean Ministries of Agriculture and Energy developed a national strategy to incorporate renewable energies into various economic sectors. Since 2013, more than 1500 off-grid solar photovoltaic (PV) systems, with power ranging from 1 kW to 3 kW, were installed to drive existing irrigation systems in small and medium-sized farms for the exportation of fresh fruit. A net billing regulation was also implemented in 2014. This study shows a cost-effective methodology for the sizing of solar PV systems for existing irrigation facilities in Chile, in an effort to improve the competitiveness of the fresh-fruit industry. The same methodology may also be implemented in other Latin American countries. The article presents the analysis of four projects (two in the Atacama Region, and two in the Maule Region). The baseline situation of the four units was studied, as well as the energy-efficient actions that may be applied, in addition to the recommended characteristics of the selected PV system to drive the irrigation systems of small fresh-fruit farms. Off-grid and on-grid solar PV systems were analyzed, including some particularities of the Chilean regulations. The required water demand of the irrigation systems and their corresponding pressure heads were also determined. The electricity demand of the system was calculated, and the PV system was designed for an optimal irrigation system. Additionally, an economical assessment was made for two years. In the first year, the cost effectiveness of energy-efficient actions was evaluated for the irrigation system, and it was found that they had paybacks of approximately two years. In the second year, the implementation of a PV system in each demonstrative unit was evaluated. The on-grid solar PV system performed better than the off-grid system, with evaluated paybacks of approximately 12 years. Finally, some recommendations for a well-designed on-grid solar PV system were made on the basis of it lasting over 25 years, with an adequate operation and maintenance plan.